(untitled) (Canadian Journal of Emergency Management, 2021)
We cannot acknowledge a new venture in Canadian emergency management coming out of 2020 without turning our thoughts to over 15,000 Canadians who have lost their lives to COVID-19 by the New Year alone. The impact and import of emergency management is reckoned in lives lost, altered, and saved.